2018
DOI: 10.1242/jcs.212563
|View full text |Cite
|
Sign up to set email alerts
|

Re-inforcing the cell death army in the fight against breast cancer

Abstract: Metastatic breast cancer is responsible for most breast cancer-related deaths. Disseminated cancer cells have developed an intrinsic ability to resist anchorage-dependent apoptosis (anoikis). Anoikis is caused by the absence of cellular adhesion, a process that underpins lumen formation and maintenance during mammary gland development and homeostasis. In healthy cells, anoikis is mostly governed by B-cell lymphoma-2 (BCL2) protein family members. Metastatic cancer cells, however, have often developed autocrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 119 publications
(164 reference statements)
0
14
0
Order By: Relevance
“…Since the approval of venetoclax for chronic lymphocytic leukemia, BH3 mimetics have bloomed as potential treatments for multiple types of cancer, predominantly hematological ( Valentin et al, 2018 ). Despite impressive experimental and clinical results as single agents, increasing evidence showed that BH3 mimetics real potential is enhancing other anti-cancer agents, both conventional chemotherapy and targeted ( Montero and Letai, 2018 ; Oudenaarden et al, 2018 ; Savona and Wei, 2019 ; Lin et al, 2020 ). Numerous studies have demonstrated that cancer cells often rely on anti-apoptotic proteins to acquire resistance to therapy, and BH3 mimetics can effectively block these adaptations ( Hata et al, 2015 ; Maji et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the approval of venetoclax for chronic lymphocytic leukemia, BH3 mimetics have bloomed as potential treatments for multiple types of cancer, predominantly hematological ( Valentin et al, 2018 ). Despite impressive experimental and clinical results as single agents, increasing evidence showed that BH3 mimetics real potential is enhancing other anti-cancer agents, both conventional chemotherapy and targeted ( Montero and Letai, 2018 ; Oudenaarden et al, 2018 ; Savona and Wei, 2019 ; Lin et al, 2020 ). Numerous studies have demonstrated that cancer cells often rely on anti-apoptotic proteins to acquire resistance to therapy, and BH3 mimetics can effectively block these adaptations ( Hata et al, 2015 ; Maji et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…If apoptosis is inhibited, however, then cells that are extruded can survive to form disorganized tissue masses. In tubular organs such as the breast this can result in occlusion of the lumens, as occurs with ductal carcinoma in situ [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The release of the BH3-only protein enables the activation of the Bax/Bak proteins [143] (Figure 6). Anti-estrogens and other agents used in ER+ breast cancer treatment such as PI3K/mTOR inhibitors and chemotherapeutics have been reported to upregulate Bcl-2 proteins, priming the cell for BH3 mimetic activity [114,130,144].…”
Section: Mitochondrial Priming For Bh3 Mimetic Activitymentioning
confidence: 99%